'Well‐leg' compartment syndrome associated with gynaecological surgery: a perioperative risk‐reduction protocol and checklist. (7th June 2021) - Addley, S; McMullan, JC; Scott, S; Soleymani majd, H
Abstract : 'Well‐leg' compartment syndrome (WLCS) is an uncommon, but potentially devastating, complication associated with prolonged patient positioning for abdomino‐pelvic surgery. Gynaecologists, anaesthetists and the wider theatre team share a responsibility to minimise the risk of this highly morbid, and even fatal, postoperative complication. This article provides an overview of WLCS related to gynaecological surgery – raising awareness amongst gynaecologists and highlighting the time‐critical nature of diagnosis and management. Given the potential litiginous nature of this complication, we also present a perioperative checklist and risk‐reduction protocol to suggest a standardised approach to prevention and relevant documentation. Tweetable abstract: Gynaecologists share a responsibility to minimise the risk of postoperative 'well‐leg' compartment syndrome. Tweetable abstract: Gynaecologists share a responsibility to minimise the risk of postoperative 'well‐leg' compartment syndrome.